Achievement of visible-light-driven Z-scheme overall water splitting using barium-modified Ta3N5 as a H2-evolving photocatalyst. Issue 1 (1st September 2016) - Qi, Yu; Chen, Shanshan; Li, Mingrun; Ding, Qian; Li, Zheng; Cui, Junyan; Dong, Beibei; Zhang, Fuxiang; Li, Can
Abstract : Barium-modified Ta3 N5 for the promotion of proton reduction is first employed as a H2 -evolving photocatalyst for visible-light-driven Z-scheme overall water splitting. Abstract : Ta3 N5 is one of the most promising photocatalyst candidates for solar water splitting, but it still remains challenging to achieve overall water splitting via Ta3 N5 -based photocatalysts regardless of whether it uses a one step or two step method. Here we will address the relatively poor photocatalytic proton reduction of Ta3 N5 with an effort for the promotion of charge separation via barium modification. One-pot nitridation of barium nitrate-impregnated Ta2 O5 precursor was adopted here for the synthesis of Ta3 N5 accompanied with the creation of a Ta3 N5 /BaTaO2 N heterostructure and surface passivation. Due to the synergetic effect of the improved interfacial charge separation and the decreased defect density, the photocatalytic H2 evolution rate of barium-modified Ta3 N5 is effectively promoted. Encouraged by this, a visible-light-driven Z-scheme overall water splitting system was successfully constructed by using the barium-modified Ta3 N5 as a H2 -evolving photocatalyst, together with a PtO x /WO3 and IO3 − /I − pair as an O2 -evolving photocatalyst and a redox mediator, respectively.